Lack of association of the vitamin D receptor gene with Graves' disease in UK Caucasians. - Collins, J; Heward, J; Nithiyananthan, R; Nejentsev, S; Todd, J; Franklyn, J; Gough, S (2004)
OBJECTIVE: Vitamin D modulates the immune system by suppressing the proliferation of activated T cells, with its actions being directed through the vitamin D receptor (VDR). A number of single nucleotide polymorphisms (SNPs) have been identified in the VDR gene, of which several have been associated with autoimmune diseases, including type 1 diabetes and Graves' disease (GD) in Japanese females. The aim of this study was to test for association of polymorphisms of the VDR gene in the genetic susceptibility to GD in UK Caucasians. DESIGN: Target DNA for five previously published SNPs, four novel SNPs and one microsatellite marker was amplified by the polymerase chain reaction (PCR). Subsequent genotyping was performed using restriction fragment length polymorphism (RFLP) or microsatellite genotyping analysis, according to the type of VDR polymorphism. PATIENTS: We obtained DNA from a case-control dataset consisting of 768 patients with GD and 864 control subjects. All patients and control subjects were Caucasians born in the UK, and all gave informed, written consent. MEASUREMENTS: Frequencies of the alleles and genotypes of the ten VDR gene polymorphisms were compared between patients and control subjects using the chi2 test. Odds ratios were calculated using Woolf's method with Haldane's modification for small numbers and D prime (D') was calculated to assess the level of linkage disequilibrium (LD) between the ten polymorphisms. RESULTS: No differences in allele or genotype frequencies were observed between GD cases and control subjects for any of the nine SNPs studied. The S allele of the PolyA microsatellite marker was slightly more frequent in GD cases when compared with control subjects (chi2= 4.364, P = 0.04). Strongest LD between markers was observed towards the 3' end of the VDR gene but there was no evidence of association with disease. CONCLUSION: This is the largest and most comprehensive study of the VDR gene in GD to date and these data suggest that these polymorphisms of the VDR gene do not contribute to GD susceptibility in the UK.